Cutaneous anthrax: evaluation of 28 cases in the Eastern Anatolian region of Turkey - Denk, Affan; Tartar, Ayse Sagmak; Ozden, Mehmet; Demir, Betul; Akbulut, Ayhan (Taylor & Francis Ltd, 2016)
Context: Anthrax is an endemic disease in developing countries. Human cases are usually associated with animal products. About 95% of naturally acquired cases are cutaneous anthrax.Objective: In this study, cutaneous anthrax cases from the Elazig province (the Eastern Anatolian region) of Turkey seen in our hospital within a 6-year period were evaluated with respect to epidemiological and clinical features, diagnosis, treatment and outcome.Methods: Twenty-eight patients with cutaneous anthrax observed between January 2009 and December 2014 were investigated retrospectively. The diagnosis of cutaneous anthrax was based on detailed history, dermatologic findings, including painless, ulcers covered by a characteristic black eschar and/or microbiological procedures, including Gram stain and culture of materials obtained from the lesions.Results: Of the 28 patients followed up with cutaneous anthrax diagnosis, 14 (50%) were female and 14 (50%) were male. The mean age of the cases was 39.6 years (age range 17-65 years). The patients have an incubation period in the range of 1-9 days (mean 4.60.5 days). The cases were seen between April and November of each year during the study period. Twenty-three cases (82%) had a history of contact with animals or animal products. Twenty patients (71.4%) showed malignant pustules and eight (28.6%) malignant edema. Bacillus anthracis was isolated in three cases (10.7%) and Gram stain smear were positive in five cases (17.8%). All patients were treated successfully with penicillin or ciprofloxacin. Systemic corticosteroids were added to the antibiotic treatment in six patients with malignant edema. Sepsis no developed in patients, all the cases recovered.Conclusion: Anthrax is still a serious public health problem in Turkey. Cutaneous anthrax must always be kept in mind when characteristic lesions such as a painless ulcer with vesicles, edema, and a history of contact with animals or animal products are observed in an individual. Early and correct diagnosis significantly affects course of the disease. Protective precautions such as vaccination of animals against anthrax and education of the population would reduce the incidence of the disease.
Keywords: Cutaneous anthrax; endemic disease; outcome; zoonosis